Nitrogen Mineralization from Sludge in an Alkaline, Saline Coal Gasification Ash Environment. Issue 3 (1st May 2013) - Mbakwe, Ikenna; De Jager, Pieter C.; Annandale, John G.; Matema, Taurai
Abstract : Rehabilitating coal gasification ash dumps by amendment with waste‐activated sludge has been shown to improve the physical and chemical properties of ash and to facilitate the establishment of vegetation. However, mineralization of organic N from sludge in such an alkaline and saline medium and the effect that ash weathering has on the process are poorly understood and need to be ascertained to make decisions regarding the suitability of this rehabilitation option. This study investigated the rate and pattern of N mineralization from sludge in a coal gasification ash medium to determine the prevalent inorganic N form in the system and assess the effect of ash weathering on N mineralization. An incubation experiment was performed in which fresh ash, weathered ash, and soil were amended with the equivalent of 90 Mg ha −1 sludge, and N mineralization was evaluated over 63 d. More N (24%) was mineralized in fresh ash than in weathered ash and soil, both of which mineralized 15% of the initial organic N in sludge. More nitrification occurred in soil, and most of the N mineralized in ash was in the form of ammonium, indicating an inhibition of nitrifying organisms in the ash medium and suggesting that, at least initially, plants used for rehabilitation of coal gasification ash dumps will take up N mostly as ammonium.